Semiconductors Industry - Importance and Challenges For The Eu Industry Development - Vlatka BILAS; Lana FRKOVIC; Matija PUCEK (Communications of International Proceedings, 2023)
Semiconductors are an essential component of all electronical devices, and therefore an essential part of our world today. With the fast-paced innovation and technological advancements, even more demand is being put on semiconductor industry every day, an industry that has already been disrupted by COVID-19 pandemic and its negative effects on global supply chains. The importance of having a strong semiconductors industry is recognised by countries in all parts of the world, as shortage of semiconductors, or chips, can, not only bring the technological advancements and electronics industry to a halt, it can also pose serious risks for national economy and safety. In line with countries like United states, China, Japan and others, EU has recognised the need to increase the competitiveness in the semiconductor industry, improve its position in the global value chain and increase resilience to disruptions in the global supply chains. In order to achieve this, EU has implemented specific measures to proactively prepare and respond to future disruptions in the supply chains, and in that way, strengthen European semiconductor industry. This paper aims to explain the importance of the topic of semiconductors in the context of today’s economy and industry, show the current state of the global semiconductor industry and processes which it involves.
Keywords: semiconductors industry; EU; innovation; competitiveness; global value chain